Physical, Chemical, and Sensory Properties of Ice Cream with the Substitution of Stabilizer with Gelatin from Various Sources - Lily Arsanti Lestari; Resha Ayu Wildiana; Fatma Zuhrotun Nisa'; Yuny Erwanto; Yudi Pranoto (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2019)
Bovine and porcine gelatin are usually used as ice cream stabilizer. However, Muslims areforbidden to consume foods that contain porcine or its derivatives product. Hence, in our previous study, wedeveloped a technique to produce gelatin from local sources such as fish, buffalo, and bovine. This studyaimed to determine the effect of various gelatin on the physical, chemical, and sensory properties of ice cream.Bovine, fish, and buffalo gelatin with the same concentration of 0.3% are added as ice cream stabilizer. Weevaluated the overrun, melting rate, viscosity, as well as the nutrient content. The sensory properties weretested using a hedonic test using a 7-point scale. The substitution of carboxymethyl cellulose (CMC) withvarious gelatin did not affect the overrun, the melting rate, ash and protein content as well as sensoryattributes (p>0.05). On the other hand, ice cream with various gelatin significantly affected the viscosity,moisture, fat, and carbohydrate content (p<0.05).